Effect of meniscus curvature on phase-change performance during capillary-enhanced filmwise condensation in porous media - Wang, Ruisong; Antao, Dion S. (Frontiers in Thermal Engineering, 2023)
Sustainably enhancing condensation heat transfer performance is a major challenge in thermal management and energy systems, since typical condensation enhancement methods (i.e., dropwise condensation with low surface energy coatings) have limited lifetime/durability, restricted compatibility with working fluids, and sustainability concerns due to the coating composition (e.g., fluorinated compounds). The robust and scalable capillary-enhanced filmwise condensation mode presented in this work demonstrates high heat transfer coefficients for water and low surface tension liquids condensing in a porous wick. Thin porous wicks offer the highest enhancements in heat transfer, however such thin porous wicks have thickness-dependent permeability, and the effective liquid thickness of the wick depends on the shape of the liquid-vapor interface. In this study, we leverage a spatially-discretized porous media model to characterize the effect of the wick thickness on condensation heat transfer performance. The model uses a spatially-varying permeability that depends on the local liquid-vapor interface shape/curvature and the resulting effective wick thickness. We apply this model to investigate the correlation between the heat transfer enhancement and various geometric factors, which enables the design of optimal porous structures for relevant phase-change application. We also predict favorable enhancement in condensation performance with a few common hydrocarbon and fluorocarbon fluid refrigerants. This study provides fundamental insight into the effects of the shape of the liquid-vapor interface on the phase-change performance in the capillary-enhanced filmwise condensation mode.